Chronic cerebrospinal venous insufficiency in multiple sclerosis: diagnostic, pathogenetic, clinical and treatment perspectives. (September 2011) - Zivadinov, Robert; Ramanathan, Murali; Dolic, Kresimir; Marr, Karen; Karmon, Yuval; Siddiqui, Adnan H; Benedict, Ralph HB; Weinstock-Guttman, Bianca
Chronic cerebrospinal venous insufficiency (CCSVI) was recently described in multiple sclerosis patients. CCSVI is characterized by impaired brain venous drainage due to outflow obstruction in the extracranial venous system, mostly related to anomalies in the internal jugular and azygos veins. The current CCSVI diagnosis is based on Doppler sonography of extracranial and transcranial venous hemodynamics criteria. To date, prevalence estimates of CCSVI, provided by different groups using various imaging methods of assessment, vary widely from none to 100%. There is an urgent need to define and validate the spectrum of cranial/extracranial venous anomalies and to establish reliable, diagnostic gold-standard test(s). The potential usefulness of endovascular treatment for CCSVI in multiple sclerosis patients is still unknown.